(untitled) (Legal journal - Research in Legal and Social Sciences, 2025)
This research focuses on the issue of criminal behavior among children and adolescents, and on the analysis of how criminal sanctions are applied in such specific cases. The main objective is to analyze the legal status of the child as an offender within the national criminal justice system, and to examine the implications of the potential lowering of the age of criminal responsibility as a proposed solution to this issue. The study is conducted through a documentary, qualitative, nonexperimental, and descriptive research design. Based on a review of national legislation and relevant legal doctrine, the findings and conclusions of this study indicate that the solution does not lie in harsher penalties, but rather in engaging both society and the State in addressing this reality. This includes promoting and enforcing the implementation of preventive mechanisms already available within the State system, in accordance with international conventions and treaties ratified by the country, as well as the National Constitution, all of which bind the State and society to the protection of children and adolescents.